2015
DOI: 10.5505/turkhijyen.2015.82542
|View full text |Cite
|
Sign up to set email alerts
|

Food disinfectants which are used in general food service systems

Abstract: The most important indicator of sanitary quality in food service system is reliable food production and service. Nowadays, the most basic approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…12 Although the antimicrobial activity of bleach as a vegetable and fruit disinfectant has been proven, it is not recommended for food disinfection because of its high residue risk. 24 Another risky cleaning behaviour is mixing different cleaning products, which is performed by almost half of the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Although the antimicrobial activity of bleach as a vegetable and fruit disinfectant has been proven, it is not recommended for food disinfection because of its high residue risk. 24 Another risky cleaning behaviour is mixing different cleaning products, which is performed by almost half of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic products may arise as a result of chemical reactions caused by mixing products containing different chemicals. 24 Bleach is a powerful disinfectant used in disinfection of COVID-19, which is composed of sodium hypochlorite active ingredients. In order to avoid the toxic effects of bleach, it is recommended not to mix it with any chemicals, use it diluted, ventilate the cleaning environment and use preservatives to prevent skin contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the high acidity content (CAC) strongly contributes to the observed antiviral response. Ayhan and Bilici informed that an acidic environment disrupts the cell wall structure causing a loss of ATP in the cell [65]. In addition, some authors reported that citric acid at a concentration of 1% effectively inactivated avian influenza virus (AIV) on hard and nonporous surfaces [66].…”
Section: Antiviral Assays Of the Chitosan-based Materialsmentioning
confidence: 99%
“…Klorlu bileşikler (sodyum hipoklorür, kalsiyum hipoklorür vb. ), asetik asit ve tuzları, ozon, sirke, kekik suyu gibi maddeler, toplu beslenme sistemlerinde etkili bir şekilde kullanılan genel amaçlı gıda dezenfektanlarıdır (Ayhan & Bilici, 2015). Koronavirüsün ortamdaki stabilitesi; sıcaklık, nem ve yüzey koşullarının yanında virüs suşu ve virüs miktarı gibi pek çok faktöre bağlıdır.…”
Section: Gıda Tüketicisi Açısından Sars-cov-2'nin Değerlendirilmesiunclassified